IMPLEMENTASI ALGORITMA BUBBLE SORT DAN SELECTION SORT MENGGUNAKAN ARRAYLIST MULTIDIMENSI PADA PENGURUTAN DATA MULTI PRIORITAS - Roma Rio Sitepu; Machudor Yusman; Febi Eka Febriansyah (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2017)
Ordering is a process of sorting data with a certain rule, so it will be arranged regularly in accordance with the rules. Basically, there are two kinds of commonly used sequencing rules: ascending and descending. In sorting data that consists of many criteria, there will be priority criteria on which the data is sorted. Priority criteria are sorted by initial criteria which are the most preferred criteria until the last criterion which is an additional criterion. In this study, researchers developed an algorithm that can help sort data that has many priorities. The algorithm used is Bubble Sort and Selection Sort, developed using multidimensional ArrayList to sort multi-priority data. The test was conducted on five times experiment and the data sorted by descending. The data used consist of four fictitious data and one real data taken from the list of all criteria of PPA 2017 scholarship recipient of MIPA faculty, University of Lampung. From the results of the tests performed, the best solution is found in the Selection Sort algorithm if compared with the Bubble Sort algorithm for multi priotity data sorting.